Research on the thought of HACCP system - WANG Tielong; YANG Qian; XU Lingyun; HOU Yang; SHI Xiaoliang (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo study the ideology within Hazard analysis and critical control point（HACCP） system， the relationship between ideology and HACCP system as well as between those ideologies.MethodsThe discipline idea contained in HACCP system were determined by investigating the connection between HACCP system and disciplines. The top six disciplines related to HACCP system were determined by expert scoring method. The correlation and significance were analyzed by Eviews software to determine significant discipline. The ideas within HACCP system and the relationship between HACCP system ideas were studied through brainstorming method.ResultsThe results showed that the subjects of food， management， mathematics， philosophy， computer and agriculture were correlated to HACCP system. Management， mathematics， philosophy and HACCP system were correlated significantly. Management， as the basis of HACCP system ideological framework， would put more focus on researches based on management theory and method extension. Mathematics， as significant tool of HACCP system research， would put more focus on analysis methods research based on mathematics， such as statistics， probability， model and so on. Philosophy， as ideology framework as HACCP system， would put more focus on ideology and view researches based on philosophy.ConclusionHACCP system contains ideologies of management， mathematics and philosophy. Management is the foundation level as the basic framework of HACCP system. Mathematics is intermediate level， as the basic theory research tool of HACCP system to support further basis research. Philosophy is the highest level as the internalized ideology of HACCP system basis theory， the ideology research of which provides scientific proof for future HACCP system theory and management research.